Influence of maximal exercise on organism`s antioxidant potential in field hockey players - Podgorski, T.; Krysciak, J.; Domaszewska, K.; Pawlak, M.; Konarski, J. (Medicina Sportiva, 2005)
56 field hockey players from Poznan field hockey clubs were investigated. Sportsmen, running on motorised treadmill performed a maximal incremental exercise test. Physiological parameters were examined on wireless portable ergospirometry system. In blood plasma we determined lactic acid and plasma antioxidant parameters (FRAP, total polyphenols, TBARS and allantoin). The tests showed that field hockey players have a high oxygen efficiency and high tolerance to effects of free radicals.